First record of rabbit carrion consumption by Eurasian Eagle-Owl (Bubo bubo) on the Iberian Peninsula - Díaz-Ruiz, Francisco; Buenestado, Francisco; Fernández-de-Simón, Javier; Ferreras, Pablo (Raptor Research Foundation, 2010)
This work was funded by the research projects CGL2005-02340/BOS and CGL2009-10741 from the Spanish I+D National Plan and cofinanced with FEDER funds. JFdS was supported by a FPI grant funded by European Social Funds and the Spanish Ministry of Science and Innovation. Peer Reviewed